Three-dimensional processing of ultrafast CT sialography for parotid masses. - Szolar, D H; Groell, R; Preidler, K; Braun, H; Stiskal, M A; Stammberger, H; Dillon, W P (American Journal of Neuroradiology, 1995)
PURPOSE To evaluate the diagnostic potential of three-dimensional image processing of ultrafast CT sialography in comparison with conventional CT sialography in patients with parotid masses. METHODS In nine patients, CT sialography was done with three-dimensional image processing. The visibility of anatomic details and pathologic findings, derived from three-dimensional images, were graded numerically by three observers and compared with the findings obtained from conventional CT sialograms. Histopathologic specimens were obtained in all cases. RESULTS Ultrafast CT images showed no motion artifact. Three-dimensional CT sialography offered significant improvement in demonstration of ductal anatomy (2.5 +/- 0.2 versus 1.5 +/- 0.1, respectively) and ductal pathology (2.6 +/- 0.1 versus 1.1 +/- 0.2, respectively) over conventional CT sialography. In two cases, the therapeutic regimen was altered substantially. CONCLUSION Ultrafast CT three-dimensional sialography has the potential to allow more precise presurgical planning and contributes to the diagnosis and therapy planning of parotid masses, especially in patients in whom MR image quality is degraded by motion artifact.